Training of Master of Ceremony for Housewives in Rt 09 Griya Sutera Balaraja - Oktariyani; Oktariyana; Hamid, Nor ‘Adha Binti AB (Jurnal Al Maesarah, 2025)
This study focuses on a community service initiative to equip homemakers in RT 09, Griya Sutera Balaraja, Tangerang Regency, with Master of Ceremony (MC) skills. The program addressed the participants who still lack public speaking proficiency, often limiting their roles in community events. Thirty housewives aged 27-33 participated in the training conducted from September 27 to 29, 2025. Using a competency-based approach, the training integrates theoretical and practical components. It is structured into six stages: orientation, motivational sessions, mindset opening, technical training, feedback provision, and follow-up activities. Participants used public speaking simulations tailored for formal and informal events, practicing voice modulation, audience engagement, and improvisation. Observation and direct assessment results revealed significant improvements in participants' confidence, material mastery, and communication skills. Feedback showed high participant satisfaction, with many recognizing the program's relevance to their personal and social responsibilities. Recommendations for future training include enhanced pre-training socialization, improved facilities, and advanced follow-up sessions to ensure long-term skill retention. In conclusion, the MC training program enhanced participants' public speaking skills and fostered community solidarity. This initiative highlights the importance of localized, need-based training in empowering individuals and addressing specific community challenges. The program serves as a replicable model for similar contexts.